Critical Assessment of Institutional and Regulatory Frameworks for Personal Data Protection in Digital Platform ecosystem: a study of Nigeria - Martha Kanene Onyeajuwa (International Telecommunications Society (ITS), 2018)
Platform ecosystem has spawned a rapidly growing data-driven economy across the globe. The emerging platform models have been adjudged to have a positive impact on quality of life by engendering economic growth. However, as technologies become more intelligent and intrusive, there is a progressively higher risk of personal data being misused or compromised. This paper seeks to study the extent to which personal data is protected in Nigeria using document analysis and complementary conversational interviews, whenever the need arises. This study finds that regulatory frameworks in Nigeria are not sufficiently focused in addressing the issues of personal data protection when compared with principles of best practice in privacy and data protection. In addition, the players (financial entities and telecoms) do not abide by fair information principles; thus, customers and citizens remain uninformed about their rights, the potential harms inherent in the services on offer and in the choices they make. The absence of a robust enforcement institution leaves the emerging platform ecosystem virtually unregulated, which provides the platform players opportunities in exploitative use of consumer data. This paper argues that lack of personal data legislation in Nigeria constitutes an obstruction to the realisation of section 37 of the 1999 Nigerian Constitution, which provides for citizen privacy and data protection. The paper further argues that the Communications regulatory framework, by limiting personal data offence to mere ST regulation 2011 infringement, plays a critical role in abstrusely commodifying customer data in ways potentially detrimental to customers. The lack of a clear legislation, despite the guarantee of citizen privacy and data protection by the 1999 Nigerian Constitution, is an indication of policy failure. Thus, this paper's focus on personal data protection is important, given the growing significance of digital platform ecosystem across the globe including Africa.
Keywords: 330; Personal data protection guidelines; platform economy; Digital Financial Services; International Telecommunication Union; Nigerian Communications Commission; Central Bank of Nigeria